Intrinsic Elements of The Novel "Kotak Waktu" by Pudjangga Lama: Structuralism Study According to Robert Stanton - Muchammad Naufal Fauqi Adhiya; Rohanda Rohanda (Gunung Djati Conference Series, 2025)
His study aims to analyze the intrinsic elements in the novel "Kotak Waktu" by Pudjangga Lama through Robert Stanton's Structuralism approach. This study uses a qualitative descriptive method. The data source in this study is the novel "Kotak Waktu" by Pudjangga Lama. Data was obtained through literature study by reading, recording, and classifying the data found in the novel "Kotak Waktu". The results of this study indicate that the novel "Kotak Waktu" by Pudjangga Lama has the theme of Existentialism and Reflection on the Journey of Time Taka and his four friends in the past and in the future, varied characters and their characterization, using a mixed plot (forward-backward), as well as setting, place, time, and style of language that build on each other. The point of view used in this novel is the third person omniscient. And the message in the novel "Kotak Waktu" by Pudjangga Lama is to always maintain relationships with fellow human beings.